Analysis of a Step-Up Approach Versus Primary Open Surgical Necrosectomy in the Management of Necrotizing Pancreatitis: Experience in a Cohort of Patients at a US Academic Medical Center. Issue 10 (November 2018) - Jones, Jason D.; Clark, Clancy J.; Dyer, Raymond; Case, L. Douglas; Mishra, Girish; Pawa, Rishi
Abstract : Objectives: An increasing number of providers have begun to use a minimally invasive step-up approach as opposed to traditional surgical necrosectomy in the management of acute necrotizing pancreatitis. Studies have shown mixed results, thus we hypothesized that the step-up approach is safer and associated with decreased mortality and length of stay (LOS). Methods: This is a retrospective cohort study of patients admitted from January 2010 to March 2015 who underwent interventions for walled-off pancreatic necrosis (WOPN). Primary outcomes included LOS after intervention and mortality, in-hospital and 90-day, with secondary outcomes of procedural complications. Results: Sixty-nine patients developed WOPN requiring intervention during the study period. In-hospital mortality was 5.6% (n = 2) in the step-up cohort compared with 18.2% (n = 6) in the surgical cohort (relative risk, 3.27; 95% confidence interval, 0.71–15.09). Ninety-day mortality was 9.1% (n = 3) in the step-up cohort and 21.9% (n = 7) in the surgical cohort (relative risk, 2.41; 95% confidence interval, 0.68–8.50). Postintervention LOS was 8 days in the step-up cohort and 17 days in the surgical cohort ( P = 0.62). Conclusions: A step-up approach, as compared with primary surgical necrosectomy in the management of WOPN, results in clinically significant decreases in mortality and LOS.